A comprehensive review of standards for distributed energy resource grid-integration and microgrid. (December 2022) - Shi, Jiaqi; Ma, Liya; Li, Chenchen; Liu, Nian; Zhang, Jianhua
Abstract: The prosperity of microgrids and distributed energy resources (DER) promotes the standardization of multiple technologies. A sound and applicable standard system will facilitate the development of renewable energy and provide great guiding significance for technology globalization. As large-scale and high penetration DER integrate, the DER are performing a more active role to support the power distribution system operation, such as active\reactive power regulation and voltage\frequency control. Thus, various market stakeholders have paid enough attention to the technical dynamic change and regional difference at the level of microgrid standard and DER grid-integration standard, including AEPS (area electric power system) operators, AEPS owners, AEPS planners, AEPS designers, AEPS dispatchers, DER developers, DER owners, equipment manufacturers and regulators. However, existing literatures and researches are concentrated on technology innovation rather than the standards application. In our paper, we comprehensively review the standards development and current situation of microgrids and DER grid-integration issued by international organizations or individual countries. Then, based on technological knowledge iteration and engineering experience, the distinction of various standards is comprehensively compared from technical, geographical, and temporal aspectes. At last, the recommendation is provided for both standard maker and audience in the field of renewable technology to better formulate and apply standard. Highlights: The distinction of various standards is compared from technical, geographical, and temporal perspectives. The dynamic change of standards is summarized at the level of DER grid-integration and microgrid level. The recommendation is proposed for standard stakeholders, such as standard maker and standard audience.